Farm machinery use and agricultural industries in India: Status, evolution, implications and lessons learned - Bhattarai, Madhusudan; Singh, Gajendra; Takeshima, Hiroyuki; Shekhawat, Ravindra S. (International Food Policy Research Institute, 2018)
This study reviews the evolution of agricultural mechanization, particularly tractors, in India. In doing so, it provides some rough indicators of the extent of mechanization (particularly the spread of tractor use) at different historical phases, emphasizing that India’s experiences up to 1990 are as important as the lessons since then. The paper highlights the growth of diverse patterns of custom-hiring service provision, as well as heterogeneity in the speed of mechanization growth across regions and agroecological zones. It also summarizes the evolution of key related policies in India that are likely to have affected tractor imports, supply, financing, manufacturing, and related inputs such as fuel and electricity.